Phase II Activity of Belinostat (PXD-101), Carboplatin, and Paclitaxel in Women With Previously Treated Ovarian Cancer. Issue 6 (1st July 2012) - Dizon, Don S.; Damstrup, Lars; Finkler, Neil J.; Lassen, Ulrik; Celano, Paul; Glasspool, Ros; Crowley, Elizabeth; Lichenstein, Henri S.; Knoblach, Poul; Penson, Richard T.
Abstract : Background: Preclinical data show that belinostat (Bel) is synergistic with carboplatin and paclitaxel in ovarian cancer. To further evaluate the clinical activity of belinostat, carboplatin, and paclitaxel (BelCaP), a phase 1b/2 study was performed, with an exploratory phase 2 expansion planned specifically for women with recurrent epithelial ovarian cancer (EOC). Methods: Thirty-five women were treated on the phase 2 expansion cohort. BelCap was given as follows: belinostat, 1000 mg/m 2 daily for 5 days with carboplatin, AUC 5; and paclitaxel, 175 mg/m 2 given on day 3 of a 21-day cycle. The primary end point was overall response rate (ORR), using a Simon 2 stage design. Results: The median age was 60 years (range, 39–80 years), and patients had received a median of 3 prior regimens (range, 1–4). Fifty-four percent had received more than two prior platinum-based combinations, sixteen patients (46%) had primary platinum-resistant disease, whereas 19 patients (54%) recurred within 6 months of their most recent platinum treatment. The median number of cycles of BelCaP administered was 6 (range, 1–23). Three patients had a complete response, and 12 had a partial response, for an ORR of 43% (95% confidence interval, 26%–61%). When stratified by primary platinum status, the ORR was 44% among resistant patients and 63% among sensitive patients. The most common drug-related adverse events related to BelCaP were nausea (83%), fatigue (74%), vomiting (63%), alopecia (57%), and diarrhea (37%). With a median follow-up of 4 months (range, 0–23.3 months), 6-month progression-free survival is 48% (95% confidence interval, 31%–66%). Median overall survival was not reached during study follow-up. Conclusions: Belinostat, carboplatin, and paclitaxel combined was reasonably well tolerated and demonstrated clinical benefit in heavily-pretreated patients with EOC. The addition of belinostat to this platinum-based regimen represents a novel approach to EOC therapy and warrants further exploration.